Micellar electrokinetic chromatography method for measuring amino acid secretions from islets of Langerhans. Issue 9 (21st April 2015) - Wang, Xue; Yi, Lian; Guillo, Christelle; Roper, Michael G.
Abstract : Islets of Langerhans are responsible for maintaining glucose homeostasis through regulated secretion of hormones and other factors. It is hypothesized that amino acids secreted from islets play a critical role in cell functionality and viability. For example, glutamate and gamma‐aminobutyric acid have been proposed to work as paracrine signaling molecules within islets to coordinate the release of hormone secretion; other amino acids, such as glutamine, leucine, alanine, and arginine, have been shown to stimulate or potentiate glucose‐stimulated insulin secretion. To characterize the potential roles that these small molecules may play in islet physiology, derivatization of amino acids in high‐salt buffers commonly used in islet experiments with naphthalene‐2, 3‐dicarboxaldehyde and MEKC separation conditions were optimized. The optimized conditions usedd ‐norvaline as the internal standard and allowed quantification of 14 amino acids with LODs ranging from 0.2 to 7 nM. The RSDs of the migration times were 0.04–0.54% and the RSDs of the peak areas were 0.2–5.8% for the various amino acids. The effects of glucose and 2, 4‐dinitrophenol on amino acid secretions from islets were tested and a suppressive effect of glucose on gamma‐aminobutyric acid release was observed, likely acting through adenosine triphosphate inactivation of glutamate decarboxylase.